Oral and Poster Presentations at the 5th Annual Congress, Sri Lanka College of Internal Medicine, 18th - 20th November 2021; Cinnamon Grand - Colombo - Suranga Ravinda Manilgama; Nirosha Madhuwanthi Hettiarachchi (Sri Lanka College of Internal Medicine, 2021)
NA